The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1371/journal.pone.0029523
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Polymorphisms Affect Expression and Function of the Neuropeptide S Receptor (NPSR1)

Abstract: Backgroundneuropeptide S (NPS) and its receptor NPSR1 act along the hypothalamic-pituitary-adrenal axis to modulate anxiety, fear responses, nociception and inflammation. The importance of the NPS-NPSR1 signaling pathway is highlighted by the observation that, in humans, NPSR1 polymorphism associates with asthma, inflammatory bowel disease, rheumatoid arthritis, panic disorders, and intermediate phenotypes of functional gastrointestinal disorders. Because of the genetic complexity at the NPSR1 locus, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 48 publications
4
36
0
1
Order By: Relevance
“…Our cell assays confirmed that stimulation of cells transfected with either NPSR1-Asn(107) or NPSR-Ile(107) with the wildtype NPS-Val(6), induced CRE activity as described previously [26, 27]. Reinscheid et al .…”
Section: Discussionsupporting
confidence: 88%
“…Our cell assays confirmed that stimulation of cells transfected with either NPSR1-Asn(107) or NPSR-Ile(107) with the wildtype NPS-Val(6), induced CRE activity as described previously [26, 27]. Reinscheid et al .…”
Section: Discussionsupporting
confidence: 88%
“…Some data have associated NPSR polymorphisms with the neuropsychiatric disorders including schizophrenia (Anedda et al 2011;Lennertz et al 2012). However, so far, limited data exists regarding the influence of neuroleptics on brain peptidergic signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…NPS binds to its cognate receptor NPS receptor (NPSR) [46] to modulate anxiety, arousal, memory and immune response. Abnormal NPS-NPSR signaling caused by NPSR gene mutation or polymorphism has been associated with pathological conditions including panic disorder [14; 41], catastrophizing [45], asthma [6], and rheumatoid arthritis[1] in human subjects. Another study in mice revealed the antinociceptive effect of NPS on inflammatory pain [44].…”
Section: Introductionmentioning
confidence: 99%